Strategi untuk Memperkuat Kebekerjaan Lulusan Perguruan Tinggi di Indonesia: Beberapa Ide untuk Masa Depan: Strategies to Enhance the Employability of Higher Education Graduates in Indonesia: A Way Forward - M Falikul Isbah; Wahyu Kustiningsih; Gregorius Ragil Wibawanto; Odam Asdi Artosa; Najib Kailani; Irsyad Zamjani (Society, 2023)
This research investigates the strategies implemented by higher education institutions in Indonesia to enhance the career sustainability of their graduates while exploring potential strengthening opportunities that need attention. The study is motivated by several significant changes, such as the expansion of a flexible job market and the uncertainty of the transition for graduates from the educational environment to the workforce. The research was conducted at eight universities in four cities from July to October 2021. The selection of these cities aimed to encompass the geographical diversity of Indonesia and represent the educational centers in each region. Data were collected through Focus Group Discussions (FGD) involving each university’s students, alumni, and career development unit managers. Three main findings emerged regarding the efforts made by the universities, including curriculum adjustments by adding entrepreneurship courses, establishing or developing career development units, and expanding networks of partners to benefit students and alumni. However, institutional capacity, human resource availability, networks, and local contexts also influenced the selection and dynamics of the applied strategies. Consequently, the achieved outcomes varied and could not be measured with uniform parameters. This research argues that policy interventions to enhance the career sustainability of university graduates should consider this complexity. Therefore, we recommend policymakers get involved in implementing independent learning and independent Campuses to understand the diverse initial conditions of universities.